Fluid structure interaction using an arbitrary lagrangian eulerian formulation - Garelli, Luciano (2012)
Fil: Garelli, Luciano. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.